THE SHRINE OF SUFI RAJAB AND THE PLACE OF SAFEKEEPING OF THE PROPHET MUHAMMAD’S KHIRQA IN THE LEZGIN VILLAGE OF HRYUG (ARABIC EPIGRAPHY OF MEDIEVAL MUSLIM SHRINES) - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2019)
The article presents the results of a study of Arabic inscriptions from a medieval Muslim shrine, located in the mountainous Lezgin village of Hryug, South Dagestan. The rich epigraphy of Hryug has not been studied until recently.The author introduces a new material of contents of the revealed Arabic construction-related inscriptions of the Muslim shrine of Sufi Rajab, located in the outskirts of the village. The discovery of the text, dated 16th century, made it possible to learn about the building of a special construction in Hryug. The building was conducted in 1565‒66 by the members of local religious elite and designed for safekeeping an Islamic relic (khirqa), which is directly mentioned in the said text. The inscription contains the names of all seven men, involved in the building of the shrine. Among them was supposedly an Arab, as indicated by the Arabic name (kunyia) Abu Hurayira. Typical Sufi references in the inscription, such as khirqa, the name of the Sufi Rajab, who directed the construction, the Sufi’s abode (khanaqah) and even details of a Sufi religious ritual, lead to a firm conclusion that this shrine was part of a Sufi complex in Hryug, likely belonging to Khalwatiya tariqa. Sufi Rajab himself was presumably a follower of Khalwatiya, which penetrated from the neighbouring Shirvan. Newly obtained scientific data on Sufism in Dagestan in the 16–17th century allow us to attribute a number of famous sheikhs and religious figures of the late medieval Dagestan to the Sufi order of Khalwatiya.The Hryug shrine was renovated more than once, as evidenced by the preserved construction-related inscriptions of 17th and 19th centuries. After the burial of Sufi Rajab in the shrine, it acquired his name among the people; and for keeping khirqa, in the last quarter of the 17th century a new building was built. Members of the local religious elite, also being skilled workers (usta), took part in its construction. Two of them (a father and a son) are mentioned in other inscriptions of the Samur region.
Keywords: the Arab epigraphy; Dagestan; the village of Krug; a feast; a sanctuary; a Sufi; Jirka; Hanaka; Sufism.